PrPSc binding antibodies are potent inhibitors of prion replication in cell lines - Beringue, V; Vilette, D; Mallinson, G; Archer, F; Kaisar, M; Tayebi, M; Jackson, GS; Clarke, AR; Laude, H; Collinge, J; Hawke, S (Elsevier, 2004)
Conversion of the cellular α-helical prion protein (PrPC) into a disease-associated isoform (PrPSc) is central to the pathogenesis of prion diseases. Molecules targeting either normal or disease-associated isoforms may be of therapeutic interest, and the antibodies binding PrPC have been shown to inhibit prion accumulation in vitro. Here we investigate whether antibodies that additionally target disease-associated isoforms such as PrPSc inhibit prion replication in ovine PrP-inducible scrapie-infected Rov cells. We conclude from these experiments that antibodies exclusively binding PrPC were relatively inefficient inhibitors of ScRov cell PrPSc accumulation compared with antibodies that additionally targeted disease-associated PrP isoforms. Although the mechanism by which these monoclonal antibodies inhibit prion replication is unclear, some of the data suggest that antibodies might actively increase PrPSc turnover. Thus antibodies that bind to both normal and disease-associated isoforms represent very promising anti-prion agents.